Desenvolvimento e caracterização de uma solução sólida de antirretrovirais: a abordagem da engenharia de cristais na obtenção de uma nova forma cristalina - Fonseca, Jéssica de Castro (2016)
Solid solutions could represent a viable alternative to better understanding and controlling structure-property relationships of drugs, in order to optimize their properties for practical applications. These phases consist of different molecular constituents randomly occupying equivalent crystallographic sites, more importantly, the stoichiometry of the solid solutions is not limited to integer values. To some extent, their composition can be controlled by simply varying the relative amount of the active ingredients to afford continuous changes in the structural parameters and properties such as density, solubility, reactivity, and others. Lamivudine (3TC) and emtricitabine (FTC) are nucleoside analogues reverse transcriptase inhibitor antiretroviral drugs. 3TC exists in two main crystalline forms, being form I a lamivudine hydrate, whose asymmetric unit contains one water and five 3TC molecules. FTC has an extremely similar molecular structure compared to 3TC, differing by a single fluorine atom, which is only present in the FTC molecule. Due to the similarities in structure and molecular size of these drugs, 3TC and FTC are good candidates for the obtainment of a solid solution, resulting in a new compound with completely different properties. This work reports the development and characterization of a solid solution containing 3TC and FTC. The solution was obtained by slow evaporation and solvent assisted mechanical activation. The stability concentration range of solvent/solute solid solution was also investigated by solvent assisted mechanical activation. The process was monitored and characterized by microscopy, spectroscopy, X-ray diffraction techniques and thermal analysis. Thus, crystal engineering contributed to the rational design of a solid solution comprising 3TC and FTC in a wide range of concentrations, which had its crystalline structure elucidated. Multicomponent crystals are a vast land for the development of new materials with different physical and chemical properties, which can be rationally tailored by varying the crystal composition. A new solid solution of organic compounds was obtained using simple execution techniques, supported with the possibility of modulating the concentration of drug inside the crystalline structure.